Antimicrobial Activity of Traditional Medicinal Plants Available at Banepa and Bhaktapur against Uropathogens (Tribhuvan University Journal of Microbiology, 2023)
Objectives: The study was aimed to determine the antimicrobial activity of traditional medicinal plants against the uropathogens.Methods: Overall, 360 urine samples were collected from both outpatient and inpatient for culture and antimicrobial susceptibility testing. All the isolates were processed and identified following standard microbiological procedure and subjected to antibiotic susceptibility testing at Microbiology laboratory of Shree Birendra Hospital following CLSI guidelines. All the three plant extracts were processed by agar well diffusion method and Tube dilution method for antimicrobial activity against Escherichia coli, Klebsiella. pneumoniae, Pseudomonas aeruginosa and Enterobacter spp. at Microbiology laboratory of Sainik Awasiya Mahavidhyalaya following standard laboratory techniques.Results: Crude extract of plants viz. Centella asiatica, Cuscuta reflexa and Mentha spicata showed good antimicrobial properties against all clinical isolates. Among all plants, ethanolic extract of C. asiatica was found to be most effective against E. coli with zone of inhibition 16 mm and minimum inhibitory concentration (MIC) value 5 mg/ml. Acetone extract of C. reflexa showed good antimicrobial activity against K. pneumoniae with zone of inhibition 14 mm and MIC value 10 mg/ml.Conclusion: Our research revealed that the crude plant extracts, particularly the acetone and ethanol extracts, had a considerable amount of efficacy against uropathogens. Based on the study results, these traditionally used medicinal plants can overcome the problems of infections caused by multidrug resistant bacteria.